Pre-service teachers’ awareness and attitude towards user-generated content as a collaborative learning tool (2015)
The promotion of learners’ active participation and becoming responsible for their own learning through the use of information communication technologies (ICT) is quite encouraging and exciting in the age of digital technologies. In particular, the Internet-based platforms and facilities that assist students in creating and sharing knowledge is becoming more popular today. This paper examined the University of Ibadan Pre-service teachers’ awareness and attitudinal disposition toward user-generated content as a collaborative learning tool with respect to their gender and teaching subject. The sample population comprised 78(42.2%) male and 107(57.82%) female 100 level students drawn from five departments where teaching subjects are offered in the Faculty of Education. A questionnaire containing students’ awareness and attitude scales (QPAAUGC), validated with Kuder Richardson 20 (reliability indices = 0.75 and 0.66 respectively) was administered to the participants. Two research questions and four hypotheses were raised and tested respectively in the study. The findings show that 63.3% of the students were aware of, and have positive attitude towards UGC. However, gender and teaching subject contributed significantly (t = 2.298, p<.05) and (F (J l82) = 13.020, p<0.05) to students’ level of awareness. Also, gender ana teaching subject contributed significantly (t g3 = 2.298, p<.05) and (F (2182) = 13.020, p<0.05) to students’ attitude to UGC as a collaborative learning tool. Premised on the findings, this paper highlights its recommendations and conclusions.